Community resilience to natural resource vulnerability due to sand mining through the application of Integrated Farming System (IFS) - Setiyo Yuli Handono; Kliwon Hidayat; Mangku Purnomo; Hery Toiba (Brawijaya University, 2023)
Changes in natural resources have presented major problems for farming communities in rural areas. In general, farmers diversify their livelihoods in the non-agricultural sector without paying attention to the impact on the availability of natural resources in the future. Sand mining activity has become one of the short-term solutions for farming communities in rural areas. As a result, a problem such as land degradation occurs in the village, thereby generating negative impacts on the availability of nature for the next generation. This study aimed to analyze the causes of land degradation and describe the Integrated Farming System (IFS) as a solution to address the land degradation problem in Bambang Village, Wajak District, Malang Regency. This study applied a qualitative case study research design, and the research methods included in-depth interviews with 40 informants, observation, and Focus Group Discussion (FGD). The location of this study was determined by purposive sampling, considering that Bambang Village is one of the villages affected by land degradation due to sand mining. The results of the study revealed that land degradation was due to the vulnerability of the farming community; thus, another alternative was proposed to utilize part of the land (20%) as a sand mining area without neglecting environmental preservation as a reward for environmental services. In addition, IFS and the actors as ecopreneurs were considered as alternative solutions to meet the needs and to prepare the farming community resilience through ecological preservation by sustaining the ecosystem balance. In practice, IFS requires integration among stakeholders, farmers and concerned institutions.